Fostering Nurses’ Support in the Workplace: Addressing Job Burnout Among Malaysian Medical Doctors Working in Public Hospitals - Omar, Nor Farehan; Md Sharif, Saiful Effendy; Mohamed Razali, Murni Zarina; Jacob, Gouri A. Dominic; Tamrin, Suraya Ika (Information Management and Business Review, 2024)
Job burnout in employees is caused by individual factors, including demographic characteristics and nurses’ support. This study analyzed the relationship between nurses’ support and job burnout among medical doctors in Malaysian public hospitals. This research was a correlational study with a cross-sectional design. The research sample was 471 employees, using the non-probability sampling method with the purposive and quota sampling techniques. Data collection used the Abbreviated Maslach Burnout Inventory (aMBI) and nurses’ support items. The data in this study were analyzed using the Statistical Package Social Science (SPSS) and Partial Least Squares Structural Equation Modelling (PLS-SEM) software. Findings suggest that 77 medical doctors who participated in the study were from Hospital Pulau Pinang, from the Emergency Department, mostly female, ranging from 24-56 years old, single, and have an MBBS education level. The study assessed the measurement model’s loading, average variance extracted (AVE), and composite reliability (CR) where the loadings were above 0.60. AVEs were greater than 0.50 and CRs were greater than 0.708. Additionally, the bootstrap BCI LL (-0.079) and UL (-0.002) for nurses’ support and job burnout were not straddled a 0 in between. Job burnout had a negative association with nurses’ support. In particular, nurses’ support towards medical doctors lowers their risk of job burnout, which has a substantial impact on medical doctors’ overall well-being. The findings indicated that medical doctors who had complete support from their nurses performed their jobs more efficiently, displayed good task performance, and experienced less job burnout.